Gene expression in vitro of colicin El plasmid. - Ebina, Y (1979)
Among eighteen polypeptides synthesized in vitro from colicin El plasmid, one of the major products with a molecular weight of 59,000 was identified as colicin El by its immunological property, molecular size, and biological activity. In addition to this polypeptide, seven other polypeptides reacted with colicin El antiserum. Using EcoRI-cleaved colicin El DNA, a 56,000 dalton polypeptide of truncated colicin El was synthesized, but no polypeptide that reacted with colicin El antiserum was produced from SmaI-cleaved colicin El DNA. This fact indicates that the direction of transcription of colicin El structural gene is from SmaI site to EcoRI site in vitro. The immunity protein of a molecular weight of 14,300 and a component of relaxation proteins of a molecular weight of 64,000 were deduced by comparing the results of the gene expression in vitro of one-half (pAO100) and a quarter (pAO2) of colicin El plasmid. The directions of transcription-translation in the genes on the plasmid were discussed. The colicin El plasmid appears to have at least three transcriptional units.